Generalized relative order (α ,β ) oriented growth analysis of composite entire functions - Biswas, Tanmay; Biswas, Chinmay (Sarajevo Journal of Mathematics, 2024)
The main aim of this paper is to study some growth properties of entire functions on the basis of their maximum modulus and generalized relative order ( α ,β )